Dukungan Keterampilan Guru Dalam Pembelajaran Pemanfaatan Media Dan Kondisi Pembelajaran Terhadap Hasil Belajar Matematikadan Dampaknya Pada Kepuasan Siswa Smp Negeri 1 Salatiga Tahun 2016/2017 - Novitasari, Meggy, Prof. Dr. Sutama, M.Pd (2017)
Meggy Novitasari A410130043. Teachers Skills In Learning, Media Utilization, And Learning Conditions Of Student Learning Outcomes Mathematics Grade VIII SMP Negeri 1 Salatiga Academic Year 2016/2017. Essay. Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta. June, 2017. Student satisfaction is important in the learning process to know the emotional state of students on the material learned in the learning. In addition, mastery of mathematics is very useful in everyday life and can support the mastery of other science. The purpose of this study is to test. 1) Contribution of teacher skill, media utilization, condition of learning to student's satisfaction indirectly through result of learning mathematics; 2) Contribution of teacher skill, media utilization, learning condition to mathematics learning result 3) Contribution of mathematics learning result to student's satisfaction.This type of research is a type of correlational research using a quantitative approach.The population in this study were 209 students. The sampling technique uses Rational Proportional Sampling by lottery. The number of samples in this study were 137 students. Technique of collecting data in this researcher use method of documentation and questionnaire method. Data analysis technique using path analysis. The results of this study indicate that. 1) Contribution of teacher's skill contribution, media utilization, learning condition to student's satisfaction indirectly through mathematics learning result, with contribution of 67%; 2) There is contribution of teacher skill, media utilization, learning condition to mathematics learning result, with contribution equal to 27%;3) There is contribution of learning result of mathematics to student satisfaction, with contribution equal to 52.85%.Keywords: teacher skills, media utilization, learning conditions, learning outcomes, student satisfaction